MODOMICS: a database of RNA modification pathways. 2021 update. Issue Volume 50:Issue D1(2022) (6th December 2021) - Boccaletto, Pietro; Stefaniak, Filip; Ray, Angana; Cappannini, Andrea; Mukherjee, Sunandan; Purta, Elżbieta; Kurkowska, Małgorzata; Shirvanizadeh, Niloofar; Destefanis, Eliana; Groza, Paula; Avşar, Gülben; Romitelli, Antonia; et al.
Abstract: The MODOMICS database has been, since 2006, a manually curated and centralized resource, storing and distributing comprehensive information about modified ribonucleosides. Originally, it only contained data on the chemical structures of modified ribonucleosides, their biosynthetic pathways, the location of modified residues in RNA sequences, and RNA-modifying enzymes. Over the years, prompted by the accumulation of new knowledge and new types of data, it has been updated with new information and functionalities. In this new release, we have created a catalog of RNA modifications linked to human diseases, e.g., due to mutations in genes encoding modification enzymes. MODOMICS has been linked extensively to RCSB Protein Data Bank, and sequences of experimentally determined RNA structures with modified residues have been added. This expansion was accompanied by including nucleotide 5′-monophosphate residues. We redesigned the web interface and upgraded the database backend. In addition, a search engine for chemically similar modified residues has been included that can be queried by SMILES codes or by drawing chemical molecules. Finally, previously available datasets of modified residues, biosynthetic pathways, and RNA-modifying enzymes have been updated. Overall, we provide users with a new, enhanced, and restyled tool for research on RNA modification. MODOMICS is available at https://iimcb.genesilico.pl/modomics/ .